2019
DOI: 10.48550/arxiv.1907.06717
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolved Massive Stars at Low-metallicity I. A Source Catalog for the Small Magellanic Cloud

Ming Yang,
Alceste Z. Bonanos,
Bi-Wei Jiang
et al.

Abstract: We present a clean, magnitude-limited (IRAC1 or WISE1 ≤ 15.0 mag) multiwavelength source catalog for the Small Magellanic Cloud (SMC) with 45,466 targets in total, with the purpose of building an anchor for future studies, especially for the massive star populations at low-metallicity. The catalog contains data in 50 different bands including 21 optical and 29 infrared bands, retrieved from SEIP, VMC, IRSF, AKARI, HERITAGE, Gaia, SkyMapper, NSC, Massey et al. (2002), and GALEX, ranging from the ultraviolet to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…For this, we used two criteria. First, we removed stars from the catalog that did not match the proper motion criteria of Yang et al (2019). These authors found that the SMC proper motion distributions fit Gaussians with µ ra = 0.695 ± 0.240 in the right ascension direction and µ dec = −1.206 ± 0.140 in the declination direction well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this, we used two criteria. First, we removed stars from the catalog that did not match the proper motion criteria of Yang et al (2019). These authors found that the SMC proper motion distributions fit Gaussians with µ ra = 0.695 ± 0.240 in the right ascension direction and µ dec = −1.206 ± 0.140 in the declination direction well.…”
Section: Discussionmentioning
confidence: 99%
“…9, that is, those with evolutionary masses in excess of 18 M and ages younger than 10 Myr. For each of these sources, we calculated their proper motion relative to the SMC by subtracting an SMC bulk motion of µ ra = 0.695 mas/yr and µ ra = −1.206 mas/yr (Yang et al 2019) from their GAIA proper motions. Then, we used their inferred age (Sect.…”
Section: C1 Star Formation Ratementioning
confidence: 99%
“…For the SMC, the method is similar to the one from Schootemeijer et al (2021): sources with a GAIA parallax over parallax error value larger than five are removed, as are sources that do not fit the proper motion criteria. More specifically, for the SMC we remove sources more than 2σ away from its bulk proper motion (µ), for which we adopt the values from Yang et al (2019): µ ra = 0.695 ± 0.240 mas/yr (Right Ascension (R.A.)) and µ dec = −1.206 ± 0.140 mas/yr (Declination (Dec.)). For the LMC, we take the same approach but for its bulk motion we adopt µ ra = 1.750 ± 0.375 mas/yr and µ dec = 0.250 ± 0.375 mas/yr, based on Fig.…”
Section: Data Setsmentioning
confidence: 99%